Microbiological Survey and Antimicrobial Resistance of Foodborne Bacteria in Select Meat Products and Ethnic Food Products Procured from Food Desert Retail Outlets in Central Virginia, USA - Chyer Kim; Brian Goodwyn; Sakinah Albukhaytan; Theresa Nartea; Eunice Ndegwa; Ramesh Dhakal (Pathogens, 2023)
In food desert areas, low-income households without convenient transportation often shop at small, independently owned corner markets and convenience stores (SIOMs). Studies indicate a higher potential for reduced product quality and safety of foods sold at SIOMs, with more critical and non-critical code violations in the region. This study aimed to assess the difference in market scale on the microbiological quality in select food products procured from food deserts in Central Virginia. A total of 326 samples consisting of meat products (i.e., ground beef, chicken, and sausage), ethnic food products (i.e., ox tail, stock fish bite, egusi ground, and saffron powder), and food packaging surfaces procured from ten registered SIOMs and nine large chain supermarkets (LCSMs) between August 2018 and March 2020 were evaluated. Higher levels of aerobic mesophile and coliform counts were found in SIOMs-acquired samples than in LCSMs-acquired samples, as demonstrated by the lower food safety compliance rate of SIOMs. Regardless of SIOMs or LCSMs, Campylobacter, E. coli, Listeria, and Salmonella were detected in 3.6%, 20.9%, 5.5%, and 2.7% of samples, respectively. The majorities of Campylobacter (75%, 6/8) and Salmonella (83.3%, 5/6) detected were from SIOMs-acquired samples including ethnic food products. Among the tested antimicrobials, AMP (100%) and TOB (100%) showed the highest frequency of resistance among Campylobacter, TCY (69.9%) among E. coli, NAL (100%) among Listeria, and TCY (50%) among Salmonella, respectively. The prevalence of multi-drug resistance (MDR) and non-susceptibility in Campylobacter and non-susceptibility in Listeria isolated from SIOMs-acquired food products were lower than those isolated from LCSMs-acquired samples. A higher price of the same brand name commodity sold at SIOMs than those sold at LCSMs was also observed, indicating an increased financial burden to economically challenged residents in food desert areas, in addition to food safety concerns. Elaborated and in-depth research on a larger-scale sample size with a greater diversity of products is needed to determine and intervene in the cause(s) of the observed differences in the prevalence of the pathogens and AMR profiles.